Radiotherapy of solitary plasmacytoma - Krause, Sonja; Hillengaß, Jens; Goldschmidt, Hartmut; Debus, Jürgen; Neuhof, Dirk (Annals of hematology, 2011)
Solitary plasmacytoma of the bone (SBP) or extramedullary plasmacytoma (EP) are rare neoplasms amenable to local radiotherapy. In this retrospective analysis, we report the University Heidelberg experience in the treatment of solitary plasmacytoma. From 1995 to 2008, 18 patients were treated with local radiotherapy. Ten patients suffered from SBP, eight patients showed a single extramedullary lesion. Local radiotherapy with a median dose of 45 Gy yielded excellent local control with only one patient suffering from local relapse. SBP and EP had significantly different 5-year multiple myeloma-free survival rates of 36.8% and 86.7%, respectively. However, no significant difference in overall survival could be detected. Radiotherapy can achieve excellent local control of solitary plasmacytoma. Progression to multiple myeloma, especially in the case of SBP, remains to be addressed by further studies.
Gesehen am 08.07.2022